Pengaruh Gaya Kepemimpinan Transformasional, Karakteristik Individu dan Budaya Organisasi terhadap Organizational Citizenship Behavior (Studi pada Pegawai Unit Donor Darah Palang Merah Indonesia Kota Yogyakarta) - Sakti, Danar Suprobo; Kirana, Kusuma Chandra; Yulianto, Eko (Ekonomis: Journal of Economics and Business, 2025)
This study aims to explore the relationship between transformational leadership, individual characteristics, and organizational culture on Organizational Citizenship Behavior (OCB) among Blood Donor Unit Employees of the Indonesian Red Cross (PMI) in Yogyakarta City. This study is an explanatory study with a quantitative approach. The research sample consisted of 59 respondents obtained by census method. Data analysis used multiple linear regression analysis. The results showed that transformational leadership has a negative and insignificant influence on Organizational Citizenship Behavior (OCB), individual characteristics have a positive and insignificant influence on Organizational Citizenship Behavior (OCB), and organizational culture has a positive and significant influence on Organizational Citizenship Behavior (OCB) among Blood Donor Unit Employees of the Indonesian Red Cross in Yogyakarta City.